A Pilot Trial of Text-Delivered Peer Network Counseling to Treat Young Adults with Cannabis Use Disorder - Mason, Michael J. (J Subst Abuse Treat, 2018)
Approximately 1.8 million young adults aged 18 to 25 had a Cannabis Use Disorder (CUD) in the past year. Unfortunately, engaging young adults in treatment is very challenging. Creative approaches to treat cannabis disorders such as integrating mobile technology with evidence-based treatments are warranted. In light of these challenges, we developed a text message-delivered version of Peer Network Counseling (PNC-txt), which is a substance use intervention that focuses on peer relations. PNC-txt engages participants in 16 automated, personalized text interactions over 4 weeks. We conducted a randomized controlled trial to test the efficacy of PNC-txt against a waitlist control group with 30 treatment seeking young adults (ages 18–25) who met DSM-5 criteria for CUD. Self-report and urine analyses were used to test outcomes at the three-month follow-up. The PNC-txt group significantly reduced their cannabis use related problems as well as cannabis cravings, compared to the control group. PNC-txt participants also had a significantly greater percentage with urines negative for cannabis metabolites compared to controls. Moderation analysis showed that CUD severity level moderated treatment, suggesting that PNC-txt is more effective for participants with medium and high levels of CUD severity. All effect sizes ranged from medium to large. Results from this pilot trial are promising and warrant further research on PNC-txt for addressing cannabis use disorder.